Retrospective analysis on the outcome of open and closed reduction of mandibular condylar fractures at tertiary centre of Gujarat - Pooja A. Patel; Amit Mahajan; Navin Shah; Rakesh shah; G.B. Ananth Kumar; Prachur Kumar Malhotra (Elsevier, 2020)
Aim: Aim of this study is to analyse the epidemiology, treatment modalities and complications faced in management of mandibular condylar fractures by surgical and conservative treatment, over period of five years at our centre. Material and method: Data of patients who were diagnosed with condylar fractures of mandible from 2013 to 2018 was collected, and were evaluated on the basis of Etiology, fracture pattern, age, sex, associated injuries, treatment modalities and complications. Results: The sample size of 82 patients (total 204), 67 male (81.71%) and 15 female (18.29%) (Male: female = 4.5:1), commonly affected 21-40 years age group. RTA is the most common cause (67.07). Subcondylar fractures were significantly related to RTA under influence of alcohol (48.5%). Total 55 (67%) were treated conservatively and (30.59%) of this belonged to MacLennan I. MacLennan II and III were mostly treated surgically with retromandibular approach being the most common. Conclusion: The principal factors which determine the treatment plan are the level of the fracture and the degree of displacement. Most of undisplaced fractures can be managed by closed non surgical treatment. Open reduction is justified mostly in adults with undisplaced or displaced fractures associated with Malocclusion and patients requiring immediate function. Even after these guidelines many other factors like Medical condition, Patient acceptance & Cost can be a deciding factor.